Penerapan Anggaran Biaya Bahan Baku dan Kinerja Pegawai Terhadap Laba Usaha Pada Perumahan Bersubsidi di Perumahan Gunung Walat Green Hill - Rizal, Rio Fariska Fahrur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The purpose of this study was to determine the effect of the implementation of the Raw Material Cost Budget and Employee Performance on Operating Profits in Subsidized Housing in Gunung Walat Green Hill Housing. The population of this research is the profit report of PT. Wandri Jaya from 2018 to 2020. In this study the researchers also used saturated sampling. Sampling is a technique when all populations are sampled. The independent variables are the raw material budget and employee performance. Secondary data collection is a source that does not directly provide data to data collectors, for example through other people or through documents. The data collected were analyzed using multiple linear regression with partial hypothesis test (t) and simultaneous test (F). The conclusion of this study is that raw materials have no partial effect on the company's profit policy, the performance of marketing employees has no partial effect on, and the raw material budget and marketing employee performance have a simultaneous effect on company performance. profit in the company PT. Wandri Jaya. In this study it can be suggested to the company PT. Wandri Jaya in meeting raw materials, the company should prioritize quality so that products meet standards, evaluate employee performance, especially the marketing department so that they continue to have good performance, through activities that have an impact on employee performance.